Price, Product Quality and Service Quality on Customer Satisfactionin Purchasing at PT. Puri Wira Mahkota Medan - William Yap; Siti Nurhaliza; Rosinta Romauli Situmeang (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of price, product quality, and service quality towards customer satisfaction. This type of research is explanatory research. The entire population is 352 store. Due to a large population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are as many as 187 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis, and the coefficient of determination as well as simultaneous test, and partial test. The results showed that price, product quality and service quality partially, andsimultaneously have a positive, and significant effect on customer satisfaction. Based on the results of this study, the implications for management are to further improve the better price, product quality and service quality.